Interrupted Ugi and Passerini Reactions: An Underexplored Treasure Island - Giustiniano, Mariateresa; Moni, Lisa; Sangaletti, Luca; Pelliccia, Sveva; Basso, Andrea; Novellino, Ettore; Tron, Gian Cesare (Synthesis, 2018)
The formation of the key short-lived intermediate nitrilium ion in the Passerini and Ugi reactions was recognized early in the discovery of these two-multicomponent transformations. Surprisingly, the idea of intramolecularly intercepting it, eluding the attack by the carboxylate, and thus interrupting the normal course of the reaction, was missed by chemists for several decades. In this review we describe, in an exhaustive manner, the reported synthetic approaches, which can be categorized as interrupted Passerini/Ugi reactions. Besides, the clear goal of this review is to show the potential of these transformations, whilst highlighting the underexplored combinations of reagents toward the identification of novel interrupted Passerini/Ugi reactions.1 Introduction2 The Interrupted Ugi Reaction2.1 The Interrupting Functional Group is Present on the Amine Reactant2.2 The Interrupting Functional Group is Present on the Isocyanide Reactant2.3 The Interrupting Functional Group is Present on the Carbonyl Reactant3 The Interrupted Passerini Reaction3.1 The Interrupting Functional Group is Present on the Carbonyl Reactant3.2 The Interrupting Functional Group is Present on the Isocyanide Reactant4 Conclusions and Future Outlook
Keywords: isocyanides; multicomponent reactions; Passerini reaction; Ugi reaction; nitrilium ions